The legal framework of post mortem fertilization in Greece and Sweden - Κηπουρίδου (Kalliopi Kipouridou) Καλλιόπη; Μιλαπήδου (Maria Milapidou) Μαρία (Bioethica, 2018)
Post-mortem fertilization is one of the most controversial methods of M.AR., the implementation of which raises a number of legal, religious, moral and social concerns. Therefore the study of the issue deserves particular attention, as the legislator is faced with unprecedented challenges. This method became possible due to cryopreservation of gametes and fertilized eggs. Several arguments have been presented both for and against this particular form of reproductive technique. Under Greek law, post-mortem fertilization is permissible provided that specific strict requirements are met according to the regulatory framework. Failure to comply with legal requirements entails civil, criminal and administrative consequences. On the contrary, the Swedish legislator has chosen to ban post-mortem fertilization, since the basic requirement to perform M.A.R. applications is that the donors of the genetic material to be alive. This restriction even excludes the use of cryoperserved fertilized eggs. However, in Sweden a debate has been developed on whether post-mortem fertilization should be allowed if the use of the method of reproductive care has begun before the death of the father or the mother. In any case, it is necessary to fully clarify all issues that arise in order to ensure legal certainty and children born through this technique are fully protected by enjoying the rights that the other children born either naturally or by using some other form of M.A.R. enjoy.